What Is It Worth? : Testing a Practical Approach to Assess and Value Natural Assets in Coastal Areas of Vietnam’s Quang Ninh Province and Tam Giang – Cau Hai Wetland in Thua Thien Hue Province - World Bank (Washington, DC : World Bank, 2022)
Inclusive and environmentally sound sustainable development requires managing natural resources that societies depend on for the long term. In the context of marine and coastal resources which provide an important source of income for large numbers of households and revenue for countries, this implies balancing the economic, social, and environmental dimensions of the use of the natural resources in marine and coastal areas. The term “blue economy” is increasingly being used to describe this balanced approach. For coastal countries such as Vietnam, the importance of its marine economy is well known. The country has used the goods and services provided by the natural assets in its near-shore and coastal areas – including fisheries, mangroves, wetlands, lagoons, and sandy beaches – for tourism, production of seafood, and controlling climate events that cause erosion and weathering. This report focuses on testing a practical approach to assess and value natural assets in select coastal areas of Vietnam. The content of the report was developed in close coordination with the provinces where the work was conducted and involved collection of primary data (during the time of COVID). The intention of this report is to provide practical example of the type of data that can be collected and compiled to estimate the extent and value of key natural assets and inform decision making.